Retrotopia. Design for Socialist Interior Spaces - Claudia Banz; Helena Huber-Doudová (Docomomo Journal)
This exhibition review, in the format of a visual essay, presents a selection of projects shown in the exhibition Retrotopia. Design for Socialist Spaces. Initiated and organized by the Berlin Kunstgewerbemuseum in 2023, Retrotopia was a comprehensive, cooperative project focusing on the role and impact of design in the countries belonging to the former Eastern Bloc and ex-Yugoslavia. Never before have these countries been represented together in one exhibition with their attendant material that helps to outline and raise awareness and understanding of the region’s design activities between the 1950s and the 1980s. Eleven design capsules were created, each highlighting two projects: one representing the public space and one the private sphere and the interior. The spectrum of interior projects and objects on display ranged from experimental housing exhibitions and cybernetic living machines to new furniture concepts, modular kitchen furniture, tableware, household tools, and toys for children.